Folate-related genes polymorphisms associated with the risk of childhood leukaemia in the Malaysian population - Siti Norfaizah Wagiman,; Noor Hamidah Husin,; Zarina Abd Latiff,; Hamidah Alias,; Rahman Jamal,; Syed Zulkifli Syed Zakaria, (Penerbit UKM, 2011)
The folate and methionine metabolism play essential roles in DNA synthesis and DNA methylation, hence their metabolic pathways might affect the susceptibility to diseases such as leukaemia. In this study, we examined the frequencies of several folate-related genes polymorphisms such as methylenetetrahydrofolate reductase MTHFR C677T and A1298C, methylenetetrahydrofolate dehydrogenase1 MTHFD1 G1958A, methionine synthase MTR A2756G and reduced folate carrier RFC1 G80A in 131 childhood leukaemia patients using PCR and PCR-RFLP techniques and determined their association with the risk of developing childhood leukaemia. An increased occurrence of childhood leukaemia was associated with MTHFR 677 CT (OR = 7.22; 95 % CI, 2.98-17.50), MTHFR 1298 AC (OR: 27.92 95% CI: 9.89-78.83) and MTHFR 1298 CC (OR: 13.25 95% CI: 4.42-39.73), RFC1 80 GA (OR: 3.95 95% CI: 1.58-9.83), RFC1 80 AA (OR: 3.83, 95% CI: 1.4-10.26), and SHMT1 1420 CT variant (OR: 5.89, 95% CI: 2.7-12.81) (p < 0.05). On the other hand, MTHFD1 1958 GA (OR = 0.42; 95 % CI, 0.20-0.90; p = 0.03) and MTRR 66 GG variant (OR = 0.05; 95 % CI, 0.01-0.29; p < 0.001) were associated with reduced risk of developing childhood leukaemia. There were no significant association of TS 3R variant and MTR 2576 A > G with the risk of childhood leukaemia variant among the 131 childhood leukaemia patients.